An Introduction to Space Instrumentation 2013
DOI: 10.5047/aisi.011
|View full text |Cite
|
Sign up to set email alerts
|

Rocket-borne Langmuir probe for plasma density irregularities

Abstract: Ionospheric plasma density exhibits very large spatial and temporal variations known as ionosphere irregularities. These irregularities are generated by a number of processes related to plasma as well as neutral dynamics. The rocket-or satellite-borne Langmuir probe (LP) is very simple and yet a very powerful tool to measure spatial variation of plasma density enabling one to study ionosphere irregularities. This article describes how a rocket-borne LP can be used to study ionosphere irregularities. It begins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The simple principle of the Langmuir probe is to expose a conducting surface biased to a potential with respect to the undisturbed plasma and to measure the collected current. The theory of Langmuir probe is well discussed in several papers (Chen, 2003;Conde, 2011;Mott-Smith and Langmuir, 1926;Sinha, 2013). Normally a Langmuir probe is subjected to a sweep voltage and the current due to the incoming plasma species is measured.…”
Section: Lp Payload Datamentioning
confidence: 99%
“…The simple principle of the Langmuir probe is to expose a conducting surface biased to a potential with respect to the undisturbed plasma and to measure the collected current. The theory of Langmuir probe is well discussed in several papers (Chen, 2003;Conde, 2011;Mott-Smith and Langmuir, 1926;Sinha, 2013). Normally a Langmuir probe is subjected to a sweep voltage and the current due to the incoming plasma species is measured.…”
Section: Lp Payload Datamentioning
confidence: 99%
“…When it is in the dissipation range the slope of the irregularity spectrum becomes more steepened and spectral index value tends to be more negative. Sinha (2013) reported that the strength of electron density irregularities follows a power law with spectral index typically ranging between 0 and −7.…”
Section: Spectral Analysismentioning
confidence: 99%